2013
DOI: 10.1097/ijg.0b013e31823298fb
|View full text |Cite
|
Sign up to set email alerts
|

Contributing Factors for Progression of Visual Field Loss in Normal-tension Glaucoma Patients With Medical Treatment

Abstract: The extent of myopia was found to be a significant positive prognostic factor for VFD progression in the upper paracentral subfield for non-high-myopic NTG eyes with an average IOP of 14.2 mm Hg under topical antiglaucoma medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 50 publications
3
39
0
Order By: Relevance
“…In other words, some studies have shown that glaucoma patients with myopia progressed faster, and other publications report that myopia is not associated with glaucoma progression. [6][7][8][9][10][11][12] Some studies [13][14][15] even demonstrate that myopia is a protective factor against glaucoma progression.…”
mentioning
confidence: 99%
“…In other words, some studies have shown that glaucoma patients with myopia progressed faster, and other publications report that myopia is not associated with glaucoma progression. [6][7][8][9][10][11][12] Some studies [13][14][15] even demonstrate that myopia is a protective factor against glaucoma progression.…”
mentioning
confidence: 99%
“…Many investigators have reported that myopia is a risk factor in NTG, 37 but the effect of myopia on the progression of glaucoma has yet to be elucidated. [38][39][40] In the current study, cluster 2 which represented mild myopia, displayed the worst VF deterioration, so we also cannot speculate on the relationship between VF progression and myopia. However, Lee et al 41 also reported that the incidence of VF progression was higher in eyes with mild myopia (> À 3 D) than in those with moderate myopia (> À6 D to < À3 D) in a group of treated POAG patients.…”
Section: Discussionmentioning
confidence: 68%
“…22,[27][28][29][30] Some studies even reported protective effect of myopia against glaucoma progression. 31 Here, we aimed to test the hypothesis that thinner ONH may be a risk factor for glaucoma progression.…”
Section: Discussionmentioning
confidence: 99%